Using a Mobile Health App (ColonClean) to Enhance the Effectiveness of Bowel Preparation: Development and Usability Study - Hui-Yu Chen; Ming-Hsiang Tu; Miao-Yen Chen (JMIR Human Factors)
Abstract BackgroundColonoscopy is the standard diagnostic method for colorectal cancer. Patients usually receive written and verbal instructions for bowel preparation (BP) before the procedure. Failure to understand the importance of BP can lead to inadequate BP in 25%-30% of patients. The quality of BP impacts the success of colonoscopy in diagnostic yield and adenoma detection. We developed the “ColonClean” mobile health (mHealth) app for Android devices. It incorporates visual representations of dietary guidelines, steps for using bowel cleansing agents, and observations of the last bowel movement. We used the Technology Acceptance Model to investigate whether the use of the ColonClean mHealth app can improve users’ attitudes and behaviors toward BP. ObjectiveThis study aims to validate the effectiveness of the ColonClean app in enhancing user behavior and improving BP, providing safe and cost-effective outpatient colonoscopy guidance. MethodsThis study uses a structured questionnaire to assess perceived usefulness, perceived ease of use, and users’ attitudes and behaviors toward BP regarding the ColonClean mHealth app. A total of 40 outpatients who were physically and mentally healthy and proficient in Chinese were randomly chosen for this study. The data were analyzed using SPSS 25.0, and we used Pearson product-moment correlation and simple regression analysis to predict the perception of ColonClean. ResultsThe results showed that 75% (30/40) of participants achieved an “excellent” or “good” level of BP according to the Aronchick Bowel Preparation Scale. Perceived usefulness and perceived ease of use of the ColonClean mHealth app were positively correlated with users’ attitudes and behaviors (P ConclusionsThe ColonClean mHealth app serves as an educational reference and enhances the effectiveness of BP. Users expressed their willingness to use the app again in the future and recommend it to family and friends, highlighting its effectiveness as an educational guide for BP.